Solvent‐ and Metal‐Free Chalcogenation of Bicyclic Arenes Using I2/DMSO as Non‐Metallic Catalytic System. Issue 32 (25th August 2017) - Silva, Lais T.; Azeredo, Juliano B.; Saba, Sumbal; Rafique, Jamal; Bortoluzzi, Adailton J.; Braga, Antonio L.
Abstract : We have developed a green and efficient protocol for the chalcogenation of bicyclic arenes by using I2 /DMSO as catalytic system under solvent‐ and metal‐free conditions. This protocol allows access to several chalcogenated bicyclic arenes through C(sp 2 )–H bond functionalization, in good to excellent yields by using microwave irradiation or conventional heating. Abstract : A green and efficient protocol for the chalcogenation of bicyclic arenes by using I2 /DMSO as catalytic system under solvent‐ and metal‐free conditions was developed. This protocol allows access to several chalcogenated bicyclic arenes through C(sp 2 )–H bond functionalization.